(untitled) (Philology, 2021)
The article deals briefly with the philosophy underlying different instruments for measuring intercultural competence and offers an Inventory for Measuring the Intercultural Competence of Students in Intensive English Language Learning Classes. It is based on Byram’s model for intercultural competence and its efficiency has been proven in research done by the author.